DIAMAS tools and resources for Diamond OA publishing (Pubmet, 2025)
The presentation discusses tools and resources for Diamond open access (OA) publishers (charging no fees to either readers or authors) and service providers, policymakers, funders, libraries and all those who practise and support Diamond OA publishing, released by the project Developing Institutional Open Access Publishing Models to Advance Scholarly Communication – DIAMAS (2022–2025). Diamond OA publishing initiatives play a crucial role in the research ecosystem. Along with offering equitable publication venues, they often support scholarly communication in native languages and foster multilingualism and bibliodiversity. However, they struggle with fragmentation, limited visibility, insufficient recognition in local and international research assessment systems and largely rely on a variety of fluctuating income streams and an unpaid workforce to carry out their work. DIAMAS activities and resources address these challenges.